Analisis Variabel Yang Memengaruhi Struktur Modal Perusahaan Otomotif Yang Terdaftar di Bursa Efek Indonesia (BEI) - Yuliani, Ni Wayan; Candraningrat, Ica Rika (E-Jurnal Manajemen; Vol 3 No 5 (2014), 2014)
This study was conducted to determine the significance of the effect of firm size, asset structure, and profitability is proxied Return on Assets (ROA) on the capital structure. Company that I use are listed automotive company in Indonesia Stock Exchange on 2008-2012 period. Through the technique of multiple linear regression analysis of the study sample was of 12 companies chosen by certain criteria. Based on the results of the analysis found that company size has a significant influence in a positive direction to capital structure, while the structure of assets and profitability is proxied Return on Assets (ROA) has significant influence with the negative direction of the capital structure of the automotive companies listed in Indonesia Stock Exchange.